An Analysis Of Figurative Language In The Song Lyrics of Map of The Soul : 7 Album - chintia nainggolan, feby (Pascasarjana Universitas HKBP Nommensen, 2024)
This study aims to find the types and the meanings of figurative language used in the lyrics of BTS songs on the album Map of the Soul: 7. The writer uses Abrams's theory (1999) in identifying the types of figurative language used. This study uses a descriptive qualitative analysis method in analyzing the data. The data were obtained from BTS songs contained in the album Map of the Soul: 7. This album has 19 songs, there are Interlude: Shadow, Outro: Ego, Intro: Persona, My Time, Black Swan, On, Filter, Friends, Moon, Inner Child, 00:00, Respect, UGH !, We Are Bulletproof: The Eternal, Jamais Vu, Dionysus, Make It Right, Boy With Luv and Louder Than Bombs. There were 53 data found. From the analysis, the writer found several types of figurative language used, there are 1 data of Synecdoche (1.88%), 1 data of Paradox (1.88%), 1 data of Sarcasm (1.88%), 1 data of Allusion (1.88%), 3 data of Apostrophe (5.67%), 3 data of Symbol (5.67%), 5 data of Simile (9.44%), 5 data of Antithesis (9.44%), 10 data of Hyperbole (18.86%), 11 data of Metaphor (20.76%), and 12 data of Personification (22.64%). The most dominant type of figurative language in the data is Personification. The writer found that BTS used some imgery on non-human objects as if they were acting like humans. In the data (2)